Dynamic Lingkages among BMSI, EMAS Index and T-Bills - Shahrol Azman, Ahmad (2005)
The Bursa Malaysia Syariah Index (BMSI) tracks all Syariah approved counter listed on the Bursa Malaysia Main Board. The Syariah approved counters have to undergo a screening process by The Syariah Advisory Council (SAC) of Securities Commission to ensure that all companies comply to the Syariah Laws. This study examines the effect of the screening activities by investigating the performance of BMSI as compared to its conventional counterpart, the EMAS Index and Malaysian three months Treasury Bills (T-bills) as a proxy for the risk free rate. In this study, cointegration analysis which is commonly used for studying investment diversification between stock markets, have been applied in examining whether the selection restriction affected the performance of BMSI and the investment diversification benefits between BMSI, and EMAS index to investors. Johansen cointegration test and vector error correction model (VECM) test are applied to check on the dynamic relationship between the BMSI, EMAS index and Malaysian three months T-Bills. This study find that in the long run all variables are significantly linked. However, in the short run, only EMAS index and BMSI have significant relationship. The results indicate that the existence of cointegration has hindered out the possibility of portfolio diversification. On the other hand, filtering criteria imposed by SAC have not adversely affect the performance of BMSI as compared to broad equity market.